Update on the Use of Botulinum Toxin Therapy for Focal and Task-Specific Dystonias - Lungu, Codrin; Ahmad, Omar F. (Seminars in Neurology, 2016)
Focal dystonia is defined by anatomical distribution and represents a distinct entity from generalized dystonia. Task-specific dystonia occurs in the context of specific patterns of movement. Botulinum neurotoxin (BoNT) injections are the treatment of choice in most cases. Several formulations are available; the approved indications, dosing, and some administration details, differ between them. The major forms of focal and task-specific dystonia are reviewed, along with the evidence for BoNT therapy, the expected benefit and side effects, and practical points guiding the injections.
Keywords: botulinum; dystonia; therapy; task-specific; focal dystonia